A GaN HEMT Structure Allowing Self-Terminated, Plasma-Free Etching for High-Uniformity, High-Mobility Enhancement-Mode Devices - Lin, Shuxun; Wang, Maojun; Sang, Fei; Ming Tao; Wen, Cheng P.; Xie, Bing; Min Yu; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Jun Xu; Cheng, Kai; et al. (IEEE ELECTRON DEVICE LETTERS, 2016)
In this letter, a plasma-free etch stop structure is developed for GaN HEMT toward enhancement-mode operation. The self-terminated precision gate recess is realized by inserting a thin AlN/GaN bilayer in the AlGaN barrier layer. The gate recess is stopped automatically at the GaN insertion layer after high-temperature oxidation and wet etch, leaving a thin AlGaN barrier to maintain a quantum well channel that is normally pinched off. With addition of an Al2O3 gate dielectric, quasi normally OFF GaN MOSHEMTs have been fabricated with high threshold uniformity and low ON-resistance comparable with the normally ON devices on the same wafer. A high channel mobility of 1400 cm(2)/V . s was obtained due to the preservation of the high electron mobility in the quantum-well channel under the gate.